Teaching and learning english in East Asian universities : global visions and local practices - Qian, David D.; Li, Lan (Cambridge Scholars Publishing, 2014)
The 25 chapters contained in this book were all written by scholars working in the field of applied linguistics and English language teaching in various East Asian contexts. East Asia is large and diverse in terms of socio-economic, linguistic, and ethnic parameters. Statistics alone cannot give a clear understanding of what goes on in rural and urban universities and what challenges English language teachers and learners face in those contexts. To understand this wide gamut of issues in English language teaching in East Asia is thus a very large undertaking. The book addresses some of these issues, arranging its 25 chapters into five sections: namely, Assessing Language Performance; Teaching English Writing; Learner Autonomy; Corpus and Discourse Research; and Learning English in East Asian Contexts. Many of the chapters in this volume concern familiar topics such as linking assessment to teaching, learning and curriculum; conducting assessment validation research; examining meta-cognitive strategies; investigating teaching and learning English for academic purposes; and profiling prevailing word lists for language learners. Other chapters are on novel or lesser known topics such as non-verbal delivery in speaking assessment; the use of visualization as a reading strategy; learner strategies in a Facebook corpus; effects of discourse signaling cues and rate of speech; and an ontogenetic analysis of college English textbooks. Collectively, these chapters showcase English language learning, teaching, and assessing in a range of contexts using a variety of methods and techniques to deal with issues relevant to East Asian teachers, learners and researchers.